In vitro assessment of berberine-loaded carboxymethyl chitosan hydrogel: A promising antimicrobial candidate for S. aureus-induced bovine mastitis treatment - Wenjia Wang; Huimin Huang; Yuetong Gu; Jiahang Li; Yian Tao; Gengshao Ma; Zhihai Shi (PLoS ONE, 2025)
Bovine mastitis poses significant challenges to the global dairy industry, leading to substantial economic losses and public health concerns. Staphylococcus aureus, a prevalent causative agent of bovine mastitis, depends on effective adhesion and biofilm formation to establish infections. Berberine (BER), a naturally occurring phytochemical, demonstrates broad-spectrum antibacterial activity but suffers from poor bioavailability. This study developed a composite berberine-carboxymethyl chitosan/sodium alginate hydrogel to address these limitations. The hydrogel was characterized using scanning electron microscopy, Fourier-transform infrared spectroscopy, and X-ray diffraction. In vitro assessments revealed that the BER hydrogel eradicated S. aureus biofilms (42% eradication at 156.26 μg/mL), inhibited bacterial adhesion, and reduced inflammatory cytokines (IL-6 and TNF-α) in S. aureus-infected MAC-T cells, with compliant biosafety biocompatibility (hemolysis rate <5%) and sustained drug release (100% over 6 h), though pH-dependent release kinetics necessitate microenvironment-specific formulation refinement. In conclusion, the BER hydrogel represents a potential therapeutic candidate for S. aureus-induced bovine mastitis.